(untitled) - Haines, Simon (Oxford, UK, 2000)
Landmark" builds on what learners bring to class and respects their knowledge and experience. Using real-life listening and reading, "Landmark" gets students thinking, noticing, and reacting
Keywords: English language; Textbooks for foreign speakers